The burden of acute pancreatitis and early experience of step-up approach for acute necrotizing pancreatitis at Military Hospital - Rawal, Sushil Bahadur; Laudari, Uttam; Khatiwada, Basanta; Thapa, Anup; Jha, Manoj Kumar; Rayamajhi, Jyoti; Malla, Srijan (Journal of Society of Surgeons of Nepal, 2019)
Introduction: Twenty-five percent of acute pancreatitis develops severe acute pancreatitis (SAP). SAP patients have prolonged hospitalization and require a substantial amount of manpower and hospital resources. The aim of this study was to give an insight into the burden of acute pancreatitis at a tertiary level military hospital and to share the experience of managing pancreatic necrosis with the application of the step-up approach.Methods: A prospective descriptive study of consecutive patients was conducted at Shree Birendra Army Hospital from 2017 June to 2017 November. Patients with a diagnosis of acute pancreatitis admitted were stratified according to severity as per Revised Atlanta classification 2012. Patients with acute necrotizing pancreatitis were enrolled for the step-up approach. Patient’s demography, baseline investigations, radiology, prognostic scoring scales and type of intervention were analyzed. The burden of severe acute pancreatitis at our center and the early experience of the step-up approach at our centre within the study period were studied.Results: Out of 35 five patients with acute pancreatitis, 7 (20%) subsequently developed severe acute pancreatitis. Among them, five patients subsequently developed necrotizing pancreatitis who were managed according to the step-up approach. Out of them, three patients subsequently underwent operative intervention in the form of minimally invasive procedures like percutaneous drain placement, laparoscopic necrosectomy, video-assisted retroperitoneal debridement, and open necrosectomy.Conclusion: Acute pancreatitis is a common presentation at our centre. The step-up approach in the management of acute necrotizing pancreatitis is a safe and feasible approach.